Ways to ensure full verification of victims and their importance in the effective use of insurance funds in Ukraine - Blazhynska, Tetiana (2025)
The purpose of this study is to analyze Ukraine’s system for verifying state insurance payments to victims of industrial accidents, assess its effectiveness, and compare it with verification models in the European Union. The research highlights significant inefficiencies in Ukraine’s current framework, including fragmented databases, delayed payments, and potential misuse of insurance funds. By contrasting this system with best practices in Germany, France, Italy, Spain, and Austria, the study identifies key deficiencies and provides policy recommendations for improvement. The findings reveal that Ukraine lacks real-time verification, automated fraud detection, and centralized data integration, leading to financial losses and delays in compensating victims. These inefficiencies place a significant burden on the state budget and pension funds, reducing the effectiveness of social protection programs and negatively impacting economic stability. In contrast, EU countries implement structured, multi-tiered verification systems, leveraging automated cross-checks, digital identity tracking, and transparent monitoring mechanisms. The study also explores the economic and social impact of ineffective verification, demonstrating how misallocated pension funds contribute to financial instability and reduced quality of life for affected workers. Using a mixed-method approach, the research combines official government data, legislative analysis, and case studies from regional pension offices to evaluate verification accuracy and fraud detection rates. The study concludes with recommendations for enhancing Ukraine’s verification process, including preventive verification, interagency database integration, and increased transparency to align with EU standards. These reforms are essential for ensuring fair compensation for victims, strengthening financial oversight, and improving social security systems in Ukraine while reducing the economic strain on public finances.